2020
DOI: 10.1177/1076029620967083
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Thromboembolism among Patients With Coronavirus Disease-19: A Systematic Review and Meta-Analysis

Abstract: Emerging evidence shows that the recent pandemic of coronavirus disease 19 (COVID-19) is characterized by coagulation activation and endothelial dysfunction. This increases the risk of morbidity, mortality and economic loss among COVID-19 patients. Therefore, there was an urgent need to investigate the extent and risk factors of thromboembolism among COVID-19 patients. English-language based databases (PubMed, Cumulative Index to Nursing and Allied Health Literature, EMBASE, and Cochrane library) were exhausti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 64 publications
(131 reference statements)
0
17
0
2
Order By: Relevance
“…We observed a significantly higher respiratory rate and lower oxygen saturations on admission in patients who were PE positive compared with the negative group. Kefale et al [16] demonstrated a pooled prevalence of 33% of thrombo-embolism in hospitalized patients with COVID-19 and this was associated with elevated concentration of D-dimer. The risk of thrombo-embolism was found to be more prevalent in those who were admitted to the ICU, in keeping with our finding that PE was more prevalent in patients who were more hypoxic and had a high respiratory rate.…”
Section: Additional Predictors Of Pementioning
confidence: 99%
“…We observed a significantly higher respiratory rate and lower oxygen saturations on admission in patients who were PE positive compared with the negative group. Kefale et al [16] demonstrated a pooled prevalence of 33% of thrombo-embolism in hospitalized patients with COVID-19 and this was associated with elevated concentration of D-dimer. The risk of thrombo-embolism was found to be more prevalent in those who were admitted to the ICU, in keeping with our finding that PE was more prevalent in patients who were more hypoxic and had a high respiratory rate.…”
Section: Additional Predictors Of Pementioning
confidence: 99%
“…Recent studies have found a significant frequency of thrombotic events in viral infections including corona-virus [ [13] , [14] , [15] ]. A meta-analysis included 8271 cases have reported thromboembolic rates in the range of 20–30% while others have reported rates as high as 40–70% [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…(19) Although D-dimer is also elevated in other conditions, such as sepsis, recent surgery and malignancy,(34) some studies have shown that D-dimer is an important predictor of VTE in COVID-19 patients. (9,21,25) A recent metaanalysis suggested that the traditional D-dimer cut-off value (<500 µg/L) used to exclude VTE in the general population seems applicable also to patients with COVID-19. (8) However, as a VTE risk predictor, there are still uncertainties about which levels would, in fact, predict a VTE.…”
Section: Machine Learningmentioning
confidence: 99%
“…(13)(14)(15)(16)) Therefore, there has been a major worldwide effort to identify predictors of VTE in hospitalized COVID-19 patients, as a path to promote prevention, early diagnosis and treatment. (8,9,(17)(18)(19) Clinical prediction scores for VTE in patients with COVID-19 are still lacking and the main available scores for clinical prediction in medical patients do not seem to perform well in patients with COVID-19. (20) Additionally, there is still a major inconsistency among the potential predictors of VTE identi ed by previous studies.…”
Section: Introductionmentioning
confidence: 99%